The link between psoriasis and other diseases based on epidemiological and genetic analyses - Adamski, Zygmunt; Kanabaj, Krzysztof; Kuźniak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Psoriasis is a chronic disease, which is associated with numerous genetic and environmental factors. The high prevalence of psoriasis worldwide (2–3% of the general population) and its various comorbidities lead to research on its pathogenesis. The aim of this article is to describe the current state of knowledge on the potential links between psoriasis and other diseases, such as inflammatory bowel diseases, uveitis, arthritis, hypertension, metabolic syndrome, diabetes mellitus, atherosclerosis, fatty liver disease, dyslipidaemia, sleep apnoea, celiac disease, lymphoma, erectile dysfunction, Parkinson’s disease, osteoporosis, chronic obstructive pulmonary disease, psychiatric disorders and substance use. Further research in this area may lead to better treatment options in the future.